Biodegradable MnO2-based gene-engineered nanocomposites for chemodynamic therapy and enhanced antitumor immunity - Yiru Wang; Ming Wu; Xiaorong Wang; Peiyuan Wang; Zhaoyu Ning; Yongyi Zeng; Xiaolong Liu; Haiyan Sun; Aixian Zheng (Materials Today Bio, 2023)
Immune checkpoint blockade (ICB) is emerging as a promising therapeutic approach for clinical treatment against various cancers. However, ICB based monotherapies still suffer from low immune response rate due to the limited and exhausted tumor-infiltrating lymphocytes as well as tumor immunosuppressive microenvironment. In this work, the cell membrane with surface displaying PD-1 proteins (PD1-CM) was prepared for immune checkpoint blockade, which was further combined with multifunctional and biodegradable MnO2 for systematic and robust antitumor therapy. The MnO2-based gene-engineered nanocomposites can catalyze the decomposition of abundant H2O2 in TME to generate O2, which can promote the intratumoral infiltration of T cells, and thus improve the effect of immune checkpoint blockade by PD-1 proteins on PD1-CM. Furthermore, MnO2 in the nanocomposites can be completely degraded into Mn2+, which can catalyze the generation of highly toxic hydroxyl radicals for chemodynamic therapy, thereby further enhancing the therapeutic effect. In addition, the prepared nanocomposites possess the advantages of low cost, easy preparation and good biocompatibility, which are expected to become promising agents for combination immunotherapy.